2015
DOI: 10.1186/s12871-015-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol dose combined with dexamethasone for PONV prophylaxis in high-risk patients undergoing gynecological laparoscopic surgery: a prospective, randomized, double-blind, dose-response and placebo-controlled study

Abstract: BackgroundLow-dose haloperidol is known to be effective for the prevention of postoperative nausea and vomiting (PONV). However, precise dose-response studies have not been completed, especially in patients at high risk for PONV who require combination therapy. This study sought to identify which dose of haloperidol 1mg or 2mg could be combined with dexamethasone without adverse effects in high-risk patients undergoing gynecological laparoscopic surgery.MethodsFemale adults (n = 150) with three established PON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…However, it is associated with risk of QTc prolongation, and it is advised to use haloperidol with caution for the prevention of PONV [30]. In the current research, haloperidol was administered at a dosage of 2 mg, and no cases of QTc prolongation or neurological syndrome were detected in group ODH, which is in accordance with previous studies [9,31] and suggests that the drugs used and their combinations were well tolerated and can be considered safe.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, it is associated with risk of QTc prolongation, and it is advised to use haloperidol with caution for the prevention of PONV [30]. In the current research, haloperidol was administered at a dosage of 2 mg, and no cases of QTc prolongation or neurological syndrome were detected in group ODH, which is in accordance with previous studies [9,31] and suggests that the drugs used and their combinations were well tolerated and can be considered safe.…”
Section: Discussionsupporting
confidence: 88%
“…These drugs appear to be similar in efficacy when used as single agents, and to exert an additive effect when in combination [8,35]. Notably, it has been identified that a combination of two types of the drugs may exert additive effect [9][10][11], such as double prophylaxis with ondansetron and dexamethasone. Whether adding a third drug could exert greater benefit has remained uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Chu et al (2008) noted two patients who experienced the EPS symptom of motor restlessness; Feng et al (2009) also noted two patients in their study experienced motor restlessness. In the study by Joo et al (2015), there were no extrapyramidal side symptoms (EPS) noted; however, in groups medicated with 2 mg of haloperidol there was increased sedation levels. Wang et al (2008) stated there were no adverse side effects of haloperidol noted.…”
Section: Resultsmentioning
confidence: 85%
“…The findings can be applied to similar population groups and the benefits were shown to be worth the harms and costs. Joo et al (2015) conducted a study (Appendix C-4) that evaluated at which dose haloperidol could be combined with dexamethasone to prevent PONV without adverse side effects in patients undergoing gynecological laparoscopic procedures. It was a clinical double-blind randomized trial.…”
Section: Resultsmentioning
confidence: 99%